Mobilizing primary biodiversity records in environmental assessments in Spain - Maite Telletxea; Rafael Miranda; Arturo Ariño; David Galicia (Biodiversity Data Journal)
Environmental Assessment is an essential tool for minimising the environmental impact of human development, generating huge amounts of biodiversity data. However, much of this information, also in Spain, remains inaccessible after being partially included in Records of Decision (RODs). As a result, these dark data remain under-utilised, limiting their potential to provide information for conservation efforts and decision-making processes.This dataset compiles 4,630 species records derived from RODs published in the Spanish Official State Gazette between 2013 and 2023, focusing on catalogued species listed in the Spanish Catalogue of Threatened Species and the List of Wild Species under Special Protection Regime. The data were collected using automated text-mining techniques and manually curated to correct errors and classify records as primary biodiversity records (PBRs), absences or literature-based occurrences. A total of 1,290 PBRs, 170 absences and 3,391 literature-based records were identified. PBRs were georeferenced and standardised according to the Darwin Core Standard. This dataset offers valuable insights into the presence and distribution of 31 non-Chiroptera species and 28 Chiroptera species, including 12 endangered (EN), 31 vulnerable (VU) and 16 listed species. The publication of these data in a FAIR (Findable, Accessible, Interoperable and Reusable) format via the Global Biodiversity Information Facility enhances their accessibility for future conservation planning and decision-making processes.